Combination of the CAGE and serum gamma-glutamyl transferase: an effective screening tool for alcohol use disorder and alcohol dependence - Choe YM (Dove Medical Press, 2019)
Young Min Choe,1,2 Boung Chul Lee,2,3 Ihn-Geun Choi,2,4 Guk-Hee Suh,1,2 Dong Young Lee,5 Jee Wook Kim1,21Department of Neuropsychiatry, Hallym University Dongtan Sacred Heart Hospital, Hwaseong, Gyeonggi, Republic of Korea; 2Department of Psychiatry, Hallym University College of Medicine, Chuncheon, Republic of Korea; 3Department of Neuropsychiatry, Hallym University Hangang Sacred Heart Hospital, Seoul, Republic of Korea; 4Department of Neuropsychiatry, Hallym University Kangnam Sacred Heart Hospital, Seoul, Republic of Korea; 5Department of Neuropsychiatry, Seoul National University Hospital, Seoul, Republic of KoreaPurpose: The CAGE is a convenient test for alcohol-related disorder due to its brevity, but it is not as effective as the alcohol use disorders identification test (AUDIT). Gamma-glutamyl transferase (GGT) is an objective blood biochemical marker of excessive alcohol intake; however, it has low sensitivity. This study tested the performance of the combined use of CAGE and GGT to screen problem drinking (PD), alcohol use disorder (AUD), and alcohol dependence (AD).Methods: A total of 394 subjects composed of 91 normal controls and 303 subjects with PD were enrolled in this study. Of the PD subjects, 147 were diagnosed with AUD (77 alcohol abuse and 70 AD). A series of multiple logistic regression models for PD, AUD, and AD discrimination were used to obtain new combined CAGE and GGT scores after adjusting for age and gender (CAGE+GGT). A receiver operating characteristic curve analysis was conducted to determine how well the CAGE+GGT score discriminated between individuals with PD, AUD, and AD.Results: The discrimination accuracy of the AUDIT for PD was significantly better than that of the CAGE or the CAGE+GGT (z=6.927, p<0.0001; z=5.301, p<0.0001, respectively). The CAGE and the CAGE+GGT were better than the AUDIT at discriminating AUD (z=2.535, p=0.0112; z=2.894, p=0.0038, respectively). The discrimination accuracy of the AUDIT for AD was significantly better than that of the CAGE and GGT (z=3.233, p=0.0012; z=6.529, p<0.0001, respectively), but the CAGE+GGT was comparable with the AUDIT (z=1.652, p=0.0985).Conclusion: Our findings support the combined use of the CAGE questionnaire and serum GGT level as a sensitive and useful tool for AD screening.Keywords: CAGE, gamma-glutamyl transferase, alcohol use disorders identification test, alcohol use disorder, alcohol dependence